2011
DOI: 10.1111/j.1537-2995.2010.02751.x
|View full text |Cite
|
Sign up to set email alerts
|

Geno‐ and phenotyping and immunogenicity of HNA‐3

Abstract: The PCR-SSP method allows reliable determination of the HNA-3a and -3b genotypes; approximately 7% of HNA-3b homozygous women develop antibodies when exposed to the HNA-3a antigen during pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
75
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(81 citation statements)
references
References 21 publications
4
75
1
1
Order By: Relevance
“…In contrast, immunogenicity of HNA-3b seems to be much lower [82], and also the clinical effect of HNA-3b alloantibodies is less severe. …”
Section: Hna-3mentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, immunogenicity of HNA-3b seems to be much lower [82], and also the clinical effect of HNA-3b alloantibodies is less severe. …”
Section: Hna-3mentioning
confidence: 99%
“…5). The HNA-3a encoding allele was demonstrated in Caucasians with a frequency of 0.79, in African Americans with 0.93 and in Chinese with 0.74, and the respective HNA-3b-encoding alleles with 0.21, 0.07 and 0.26 [82,83,84]. An additional SLC44A2*451C>T exchange (rs147820753) affecting the amino acid next to Arg152 and inducing a Leu151Phe substitution impairs the HNA-3a epitope in a way that the induction of neutrophil agglutination by some HNA-3a-specific alloantibodies is diminished or even abrogated [85].…”
Section: Hna-3mentioning
confidence: 99%
“…1 Although the pathogenesis of TRALI is only partially resolved, an increasing number of studies have confirmed the role of antibodies against HLA and HNA antigens in the development of TRALI. [2][3][4][5][6] Recent case control studies have shown that HLA Class I antibodies are weak triggers of TRALI compared to HLA Class II and HNA antibodies, [7][8][9] and a smaller study even debated the involvement of HLA antibodies at all. 10 TRALI accounted for 47% of the transfusion-related fatalities reported to the US Food and Drug Administration from 2005 through 2010.…”
mentioning
confidence: 99%
“…Genotyping methods recently were developed based on the molecular characterization of HNA-3 32,33 that could allow for screening of donors at risk of developing HNA-3a antibodies (eg, previously pregnant women). Reil et al recently developed such a method using polymerase chain reaction sequence-specific primers to genotype HNA-3a and HNA-3b of 398 blood donors.…”
Section: Hna Genotypingmentioning
confidence: 99%